Utilization of Solid Biomass Waste (Oil Palm Frond) as Low-Cost Adsorbent for Janus Green B Dye Removal - Husni, Hasrul (IRC, 2016)
Dye waste in water pollution has become a major environmental issue that causes insecurity, health disorder and interference with the nature’s law of ecological balance. As we advance in the modern world, strict legal limits imposed on waste water discharge has urged the needs for new technical applicability and cost-effective method for water treatment. Recently, the study of using raw biomass for removing dye has drawn attention of various researchers. It is highly recommended to develop a low-cost adsorbent from agricultural waste or industrial by-product that will add value to the waste. Thus, this project aimed to evaluate the potential of oil palm frond (OPF) in removing Janus Green B (JGB) dye. The prepared biomass were subjected to dye adsorption studies and the effect of pH, initial dye concentration and biomass loading were studied. The adsorption capacity increased with an increased in initial dye concentration.